2014
DOI: 10.1037/a0035559
|View full text |Cite
|
Sign up to set email alerts
|

Rainmakers: Why bad weather means good productivity.

Abstract: People believe that weather conditions influence their everyday work life, but to date, little is known about how weather affects individual productivity. Most people believe that bad weather conditions reduce productivity. In this research, we predict and find just the opposite. Drawing on cognitive psychology research, we propose that bad weather increases individual productivity by eliminating potential cognitive distractions resulting from good weather. When the weather is bad, individuals may focus more o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 70 publications
4
25
1
Order By: Relevance
“…We recruited 400 fulltime employees (51% women, 49% men; mean age 35.5 years; current organizational tenure 5.88 years) who had worked for their current organizations for at least 6 months from Amazon Mechanical Turk (MTurk). Results from employees recruited through MTurk are similar to those from employees recruited using traditional methods that are commonly used in organizational behavior research (Adam & Shirako, 2013;Kouchaki & Desai, 2015;Lee, Gino, & Staats, 2014).…”
Section: Participants and Proceduresmentioning
confidence: 59%
“…We recruited 400 fulltime employees (51% women, 49% men; mean age 35.5 years; current organizational tenure 5.88 years) who had worked for their current organizations for at least 6 months from Amazon Mechanical Turk (MTurk). Results from employees recruited through MTurk are similar to those from employees recruited using traditional methods that are commonly used in organizational behavior research (Adam & Shirako, 2013;Kouchaki & Desai, 2015;Lee, Gino, & Staats, 2014).…”
Section: Participants and Proceduresmentioning
confidence: 59%
“…Recent studies have demonstrated operational policies such as scheduling and staffing (Chan et al 2014;Dai et al 2015;Huckman and Staats 2011), monitoring and transparency (Bernstein 2012;Buell et al 2016;Staats et al 2016;Tan and Netessine 2015), performance recognition (Gubler et al 2016;Song et al 2016), and workflow (Kuntz et al 2014;Staats and Gino 2012;Tan and Netessine 2014) can all profoundly impact worker performance. Even environmental factors outside managerial control, such as weather (Lee et al 2014), are being revealed as determinants of individual and group productivity. Our study uniquely contributes to this literature not only by showing the link between health and productivity, but also by supporting the growing argument that firm policy can broadly improve operations through worker health and well-being (Ton 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Task performance was measured using two indices, namely, the number of spelling mistakes detected and a time measure calculated by a log transformation of the average time spent on the task divided by the number of spelling mistakes correctly identified (Lee et al, 2014).…”
Section: Study 1: Academic Task Performancementioning
confidence: 99%